ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERPUTARANPIUTANG, RASIO HUTANG, DAN OPERATING CYCLE TERHADAP LIKUIDITAS (Studi Kasus Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2007 -2010) - VP, Anastasia; Haryanto, Mulyo (Diponegoro Journal of Management, 2013)
The amount of liquidity through current ratio (CR) in food and beverage companies experienced significant changes over period 2007-2010. Liquidity is important area in financial management because it refers to the availability of the current assets of the business to pay offthe current liabilities. Liquidity reflects the management of short-term assets and liabilities of the firms with the maturities of less than a year. Continuous monitoring is required to maintain optimum levels of various components of liqudity. This study aims to analyze the factors that influence toward the corporate liquidity. The population in this research is taken from food and beverage companies which enlisted in the BEI from year 2007 - 2010. The samples are obtained by using the purposive sampling method until only 16 companies left to be taken as samples in this research. This research uses regression analysis method to find the effect of independent variables, such as profitability,Â  size, receivable turnover , debt ratio , and operating cycleBased on the result of regression analysis for five independent variables, there are only receivable turnover and operating cycle that have a significant effect on the corporate liquidity. While the other variables such as profitability, size, and debt ratio have no significant effect on the corporate liquidity in food and beverages companies sector which enlisted in the BEI from year 2007 â€“ 2010.